Proposed exercises to adjust the approach run and its effect on some bio-kinematic variables, and the lost horizontal distance for performance of long jump at age of (13-15) - Dakhil, Ehab (Journal of Physical Education, 2017)
The study consisted of five chapters:Chapter one included the introduction and the importance of the study which is summed up in setting up trainings to contribute to the adjustment of the approach run accuracy by reducing the lost distance and developing the official distance through some kinematic variables of long jump.The study aimed at: •setting up trainings to develop the adjustment of approach run at age of(13-15)•identifying the effect of these trainings on the approach run and some kinematic variables at age (13-15)•identifying the effect of these trainings on the lost horizental distance for performance at age (13-15) The hypotheses of the study:•There are significant differences between the pre and post measures in some kinematic variables at age (13-15)•There are significant differences between the pre and post measures in approach run and the lost horizontal distance for performance at age (13-15)Chapter Two includes some topics related to the study such as sports training, junior training, long jump event, and some particular biomechanical variables related to the study.Chapter Three tackles the method of the study and its procedures. The researcher has used the experimental method of one group design which conveniently meets the nature of the problem. The subject of the study consists of (10) jumpers recorded in the National Center of Nurturing Sports Talents in Athletics; represent 100% of the original community. A pilot experiment has been applied by the researcher to help in the adjustment of the main experiment lately. Body weight, leg length, and shoes size have been measured. To conduct the long jump test, the researcher has used two (2) cameras and a foot scan device to extract the biomechanical variables of the study. Finally, the results have been statistically treated using the Statistical bag (SPSS)